2003
DOI: 10.1097/01.asn.0000050415.97942.2f
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Contribution of Three Mitogen-Activated Protein Kinases to PDGF-BB-Induced Mesangial Cell Proliferation and Gene Expression

Abstract: Abstract. This study examined the role of mitogen-activated protein (MAP) kinase in PDGF-BB-induced proliferation and gene expression of human mesangial cells (MC). PDGF-BB stimulation of MC increased mRNA for transforming growth factor-␤1 (TGF-␤1), monocyte chemoattractant protein-1 (MCP-1), and plasminogen activator inhibitor-1 (PAI-1) and increased the cell numbers. To inhibit activation of extracellular signal-regulated kinase (ERK), c-Jun amino-terminal kinase (JNK), and p38, MC were infected with recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
(38 reference statements)
6
30
0
Order By: Relevance
“…MAPK signaling pathways, which promote cell cycle progression by regulating the expression of cyclin-dependent kinases, are critically involved in the proliferation of mesangial cells (17). Our findings in this study indicated that ERK1/2, JNK, and p38 MAPK signaling was activated in mesangial cells exposed to high glucose, which might be an important molecular mechanism responsible for mesangial cell proliferation.…”
Section: Discussionmentioning
confidence: 49%
“…MAPK signaling pathways, which promote cell cycle progression by regulating the expression of cyclin-dependent kinases, are critically involved in the proliferation of mesangial cells (17). Our findings in this study indicated that ERK1/2, JNK, and p38 MAPK signaling was activated in mesangial cells exposed to high glucose, which might be an important molecular mechanism responsible for mesangial cell proliferation.…”
Section: Discussionmentioning
confidence: 49%
“…In renal tubular epithelial cells, the MEK inhibitor U0126 prevents induction of MCP-1 in response to a variety of stimuli, including TNF-␣, albumin, and osmotic stress (27,34,71). In MCs, a dominant-negative ERK construct inhibits PDGF-stimulated MCP-1 production (31). We previously demonstrated that n-3 fatty acids decrease EGF-stimulated ERK activation in cultured MCs (78).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of c-Jun induces MCP-1 gene expression (Wang et al, 1999). JNK is also involved in MCP-1 expression in other cell types, including renal mesangial cells (Kawano et al, 2003) and vascular smooth muscle cells (Chen et al, 2004), but previous data on the involvement of JNK in MCP-1 expression in cultured human and mouse tubular epithelial cells have been conflicting (Tsuboi et al, 2002;Sengul et al, 2003).…”
Section: Discussionmentioning
confidence: 99%